Note su Flamenca. - Lazzerini, Lucia; Manetti, Roberta (Scripta, 2022)
The present paper consists of two independent, but complementary contributions on some critical issues concerning the Occitan romance known as Flamenca, a very refined text which, like all great literary works of the Middle Ages, allows multiple levels of reading. In the first part, we put forward a new hypothesis as regarding a long debated crux. In the second one, we assess again why the most correct interpretation of the chronological clues disseminated in the work should date the composition of the romance back to the forties of the thirteenth century (against the thesis that would place it in the last quarter).